Planning and execution of catheter closure of a giant left atrial appendage aneurysm causing recurrent cardioembolism - Sivakumar Kothandam; Rajeshkumar Ramasamy (Wolters Kluwer Medknow Publications, 2020)
Giant left atrial appendage aneurysms (LAAAs) are rare causes of recurrent cardioembolism and managed routinely by surgery. A first catheter closure of a giant LAAA is reported, when a recent cerebral infarct precluded immediate surgery. Planning included ostial measurement on multimodal imaging, echo navigation for septal puncture, rotational angiogram for profiling, overlay imaging for device placement, and cerebral embolic protection from thrombus debris.